Financing Sustainable Agriculture Under Climate Change - Ji-kun HUANG; Yang-jie WANG (Journal of Integrative Agriculture, 2014)
Agriculture is facing great challenge in meeting global food security and is expected to face even greater challenge under climate change. The overall goal of this paper is to examine how finance can be used to achieve the joint objectives of development, mitigation of and adaptation to climate change in agriculture in developing world based on literature review. The results show that agriculture is much under invested and foreign aid also has not increased appropriately to assist developing countries to maintain sustainable agriculture under climate change. There are a wide range of areas in mitigation of and adaptation to climate change that need substantial investment. Major areas and successful cases mitigation of and adaptation to climate change in agriculture that have worked in developing countries are examined. A list of areas that have worked, could work and be scaled up or transferred is identified and discussed. This study concludes that mainstreaming agricultural mitigation and adaptation into agricultural development programs, enhancing local capacity, and considering different stakeholders' needs are major experiences for successfully financing sustainable agriculture under climate change.